Pioglitazone restores phosphorylation of downregulated caveolin-1 in right ventricle of monocrotaline-induced pulmonary hypertension. (17th February 2022) - Malikova, Eva; Kmecova, Zuzana; Doka, Gabriel; Pivackova, Lenka Bies; Balis, Peter; Trubacova, Simona; Velasova, Eva; Krenek, Peter; Klimas, Jan
ABSTRACT: Background: Caveolin-1 (cav-1) plays a role in pulmonary arterial hypertension (PAH). Monocrotaline (MCT)-induced PAH is characterized by a loss of cav-1 in pulmonary arteries; however, less is known regarding its role in the hypertrophied right ventricle (RV). We aimed to characterize the role of cav-1 and Hsp90 in the RV of MCT-induced PAH and their impact on endothelial nitric oxide synthase (eNOS). Additionally, we focused on restoration of cav-1 expression with pioglitazone administration. Methods: Male 12-week-old Wistar rats were injected subcutaneously with monocrotaline (60 mg/kg). Selected proteins (cav-1, eNOS, pSer1177eNOS, Hsp90) and mRNAs (cav-1α, cav-1β, eNOS) were determined in the RV and left ventricle (LV) 4 weeks later. In a separate MCT-induced PAH study, pioglitazone (10 mg/kg/d, orally) administration started on day 14 after MCT. Results: MCT induced RV hypertrophy and lung enlargement. Cav-1 and pTyr14cav-1 were decreased in RV. Caveolin-1α (cav-1α) and caveolin-1β (cav-1β) mRNAs were decreased in both ventricles. Hsp90 protein was increased in RV. eNOS and pSer1177eNOS proteins were unchanged in the ventricles. eNOS mRNA was reduced in RV. Pioglitazone treatment increased oxygen saturation and pTyr14cav-1 vs. MCT group. Conclusions: Restoration of pTyr14cav-1 did not lead to amelioration of the disease, nor did it prevent RV hypertrophy and fibrosis, which was indicated by an increase in Acta2, Nppb, Col3a1, and Tgfβ1 mRNA.